The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18632/oncotarget.12628
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of combined expression of B7-H3 and B7-H4 as prognostic marker in esophageal cancer patients

Abstract: The co-stimulatory ligands of B7-family have been confirmed to play an important role in negatively regulating the T-cell mediated anti-tumor immunity. In addition, these inhibitory molecules are also aberrantly expressed on various human cancers tissues, and significantly associated with cancer progression and patients' poor prognoses. We have previously reported that B7-H3 and B7-H4 ligands are highly expressed in human esophageal cancer tissues. Herein, we tried to further analyze the value of their combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…More recently, combination with B7 family molecules has been used to enhance the sensitivity and specificity of prediction. Previous studies have determined that the combination of B7-H3 and B7-H4 may be used as a novel prognostic marker for esophageal cancer (29), and that T lymphocytes plus enoblituzumab (B7-H3 antibody) can inhibit tumor growth in renal and bladder carcinoma xenografts (30). Furthermore, the B7-H2 antibody JTX-2011 has shown success in the phase 1 ICONIC clinical trial (NCT02904226) (31).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, combination with B7 family molecules has been used to enhance the sensitivity and specificity of prediction. Previous studies have determined that the combination of B7-H3 and B7-H4 may be used as a novel prognostic marker for esophageal cancer (29), and that T lymphocytes plus enoblituzumab (B7-H3 antibody) can inhibit tumor growth in renal and bladder carcinoma xenografts (30). Furthermore, the B7-H2 antibody JTX-2011 has shown success in the phase 1 ICONIC clinical trial (NCT02904226) (31).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study 13 , we reported the negative roles of B7-H4 in the proliferation, apoptosis, migration and invasiveness of cervical cancer cells as well as the diagnostic value of serum B7-H4. In addition, an increasing number of reports has suggested that B7-H3 may exert effects that are similar to those of B7-H4 8 , 20 , which prompted us to perform this study. Many studies have reported that P16 serves as a useful additional marker for the interpretation of problematic TCT and that its assessment reduces uncertainty during the evaluation of suspicious biopsies of the uterine cervix in patients with CIN and cervical cancer 21 - 24 .…”
Section: Discussionmentioning
confidence: 99%
“…B7-H4 is frequently deregulated in human cancers including breast cancer 7 , gastric cancer 8 , gallbladder carcinoma 14 , and esophageal cancer 15 . In this study, we showed that B7-H4 expression was raised in bladder cancer cells relative to normal human urothelial cells, which was consistent with clinical data that showed an upregulation of B7-H4 in UCC 10 .…”
Section: Discussionmentioning
confidence: 99%